2018
DOI: 10.1371/journal.pone.0206384
|View full text |Cite
|
Sign up to set email alerts
|

Cough-aerosol cultures of Mycobacterium tuberculosis in the prediction of outcomes after exposure. A household contact study in Brazil

Abstract: BackgroundMycobacterium tuberculosis cultures of cough-generated aerosols from patients with pulmonary tuberculosis (TB) are a quantitative method to measure infectiousness and to predict secondary outcomes in exposed contacts. However, their reproducibility has not been established.ObjectiveTo evaluate the predictive value of colony-forming units (CFU) of M. tuberculosis in cough aerosols on secondary infection and disease in household contacts in Brazil.MethodsAdult sputum smear+ and culture+ pulmonary TB ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“… 34 A consistent finding in tuberculosis aerosol studies is the variability of infectious aerosol production from patients with pulmonary tuberculosis. 33 These data suggest that a few patients with tuberculosis are infectious via cough aerosols, and some are very infectious, 41 coherent with the epidemiological observation of super-spreading. 42 , 43
Figure 1 Particle size distributions of cough aerosols from (A) patients with tuberculosis 24 and (B) patients with cystic fibrosis infected with Pseudomonas aeruginosa 27 (A) Reproduced from Fennelly et al, 24 by permission of the American Thoracic Society.
…”
Section: Cough Aerosol Studiesmentioning
confidence: 60%
See 1 more Smart Citation
“… 34 A consistent finding in tuberculosis aerosol studies is the variability of infectious aerosol production from patients with pulmonary tuberculosis. 33 These data suggest that a few patients with tuberculosis are infectious via cough aerosols, and some are very infectious, 41 coherent with the epidemiological observation of super-spreading. 42 , 43
Figure 1 Particle size distributions of cough aerosols from (A) patients with tuberculosis 24 and (B) patients with cystic fibrosis infected with Pseudomonas aeruginosa 27 (A) Reproduced from Fennelly et al, 24 by permission of the American Thoracic Society.
…”
Section: Cough Aerosol Studiesmentioning
confidence: 60%
“…Studies of those that included methods to measure particle sizes have consistently found pathogens in small particles (ie, <5 μm; table 1 ). Other studies without particle size data focused on other outcomes, 16 , 33 , 34 or used methods that could not provide sizing data. 35 , 36 , 37 , 38 , 39 , 40 …”
Section: Cough Aerosol Studiesmentioning
confidence: 99%
“…The present study included data from 3 cohorts of adult patients (aged ≥18 years) with pulmonary tuberculosis, cohorts with near-identical inclusion criteria. The studies were conducted in Uganda and Brazil over a 13-year period [11, 12, 14].…”
Section: Methodsmentioning
confidence: 99%
“…Since first demonstrating the feasibility of culturing M. tuberculosis directly from cough-generated aerosol samples in 2004 [10], our group has completed several studies showing that the number of colony-forming units (CFUs) of M. tuberculosis in aerosol samples is a quantitative and more precise marker of infectiousness than sputum AFB smear [11–13], and have demonstrated reproducibility [14]. In studies from Uganda and Brazil, household contacts of the minority of tuberculosis cases with high aerosol CFU counts (≥10 CFUs) were found to have both a higher risk of infection—as measured by qualitative and quantitative readouts of tuberculin skin test and interferon gamma release assay—and higher rates of secondary tuberculosis disease during follow-up [13, 14]. Therefore, elucidating which host, environmental and bacterial factors are associated with M. tuberculosis aerosolization will provide fundamental insights into the pathogen’s aerobiology and may lead to interventions to interrupt transmission.…”
mentioning
confidence: 99%
“…6 Subsequent cohorts of smear-positive culture-proven TB patients from Uganda and Brazil found that 100/233 (43%) patients produced culturable aerosols and of these 57 (24%) were high aerosol producers defined as production of ≥ 10 colony forming units (CFU) of M. tuberculosis from aerosol sampling. [7][8][9] Two other studies from South Africa have been done, one using a minor modification of the CASS method 10 and the other a novel stationary respiratory air sampling chamber in which the whole patient sits. 11 Infectious aerosol production has been found to be only partially related to bacterial burden measured as AFB smear grade or time to positivity in liquid culture media, and it appears to decrease rapidly after commencement of TB therapy.…”
Section: Tuberculosismentioning
confidence: 99%